2010
DOI: 10.1002/ajpa.21322
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between morphological and genetic data to estimate biological relationship: The case of the Egyin Gol necropolis (Mongolia)

Abstract: Osseous and dental nonmetric (discrete) traits have long been used to assess population variability and affinity in anthropological and archaeological contexts. However, the full extent to which nonmetric traits can reliably be used as a proxy for genetic data when assessing close or familial relationships is currently poorly understood. This study represents the unique opportunity to directly compare genetic and nonmetric data for the same individuals excavated from the Egyin Gol necropolis, Mongolia. These d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 62 publications
2
63
0
7
Order By: Relevance
“…Unlike osteometric stature or sexual dimorphism, they were not population specific. Similarly in a study on discrete traits and familial (genetic) relationships, Ricaut et al [18] found positivealbeit low -correlations between the two variables. In line with other researchers, they cautioned the use of discrete traits as a means to explain assumed genetic differences between groups.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Unlike osteometric stature or sexual dimorphism, they were not population specific. Similarly in a study on discrete traits and familial (genetic) relationships, Ricaut et al [18] found positivealbeit low -correlations between the two variables. In line with other researchers, they cautioned the use of discrete traits as a means to explain assumed genetic differences between groups.…”
Section: Discussionmentioning
confidence: 80%
“…Yet, many researchers are unsure about these traits being valid measures in discerning population differences, particularly among admixed groups such as ''Coloured'' South Africans [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Both acknowledge the value of skeletal variants in bioarchaeological studies at these geographic scales. Ricaut et al (2010) found that combined morphological data provided good resolution in identifying pairs of kin within a Mongolian necropolis, although genetic findings detected double the number. In the second study, Herrera et al (2014) compared Y-chromosome, mtDNA, cranial metric, and cranial morphology data in samples from the Bering Strait region; they found that craniometric distances were correlated with mtDNA, while distances based on cranial morphology were correlated with those from Ychromosome variants.…”
Section: " "mentioning
confidence: 95%
“…In the second study, Herrera et al (2014) compared Y-chromosome, mtDNA, cranial metric, and cranial morphology data in samples from the Bering Strait region; they found that craniometric distances were correlated with mtDNA, while distances based on cranial morphology were correlated with those from Ychromosome variants. Viewed as a whole, two lessons can be learned from the present and previous studies: 1) additional work needs to be undertaken to determine which skeletal and genetic data are best suited to answer particular research questions (Herrera et al, 2014;present study); and 2) care should be taken when formulating very fine scale interpretations of population history from skeletal data (Ricaut et al, 2010;present study;also Scott and Turner, 1997).…”
Section: " "mentioning
confidence: 96%
See 1 more Smart Citation